Analysis of the Role of Fatwa Institutions in Developing Alternatives to the Mudharabah Agreement in Sharia Financial Institutions - Sinta Thia Anggraeni; Muthoifin (Walidem Institute and Publishing (WIP), 2024)
This study aims to examine fatwas from various organizations on alternative mudharabah contracts in Islamic economics. The mudharabah contract implements a profit-sharing mechanism between capital owners (rabbul mal) and business managers (mudharib). Fatwa institutions provide change and alternatives because these contracts often face obstacles such as the possibility of moral hazards and supervision problems. The methods used are qualitative, such as document analysis, comparative studies, legal analysis, historical research, in-depth interviews, and focus groups. The researcher studied nine fatwas from various organizations, including the World Sharia Economic Council, Bank Indonesia's Sharia Committee, DSN-MUI, AAOIFI, JAKIM, MUI, Al-Azhar University, and the Muhammadiyah Tarjih Council. The test highlights the importance of regulatory compliance, innovation, openness, accountability, and flexibility in profit-sharing arrangements. Concepts such as mudharabah musytarakah, mudharabah muqayyadah, and hybrid schemes between mudharabah and other contracts such as musharakah and ijarah are proposed by these fatwas. The results of the study concluded that these fatwas provide creativity and adaptation to build fairer, more transparent, and effective corporate collaborations in line with sharia principles. They also provide insight to scholars and practitioners in making and implementing mudharabah contracts in various circumstances.